Preliminary Characterization of Structural and Rheological Behavior of the Quinoa Hyperprotein-Defatted Flour - Ortiz-Gómez, Vicente; Nieto-Calvache, Jhon Edinson; Roa-Acosta, Diego Fernando; Solanilla-Duque, Jose Fernando; Bravo-Gómez, Jesús Eduardo (Frontiers in Sustainable Food Systems, 2022)
Protein functional properties are related to physical and chemical parameters that influence protein behavior in food systems during processing, storage and consumption. The structural and rheological properties of three quinoa hyperprotein flours (without defatting, WD, chemically defatted, CD, and mechanically defatted, MD) were evaluated. The values of the fluidity index (n) were significantly different (p < 0.05), which was associated with changes in protein or starch structures due to solvent treatments or heating of the flour during pressing. In addition, a strong dependence of the consistency index (k) on the shear rate was observed. For dispersions with a concentration of 12% (w/v), CD and WD had a significantly lower setback value than MD. The viscosity peak was affected by the presence of lipid molecules. Greater changes were evident in the β-sheet (1,610 and 1,625 cm−1) and β-spin (1,685 and 1,695 cm−1) structures. The changes identified in these structures were associated with the defatting treatment. Consequently, the intensity ratio 2,920/1,633 cm−1 was more sensitive to changes in the fat content of the flours. It was shown that defatting conditions increase the protein adsorption kinetics and that the viscoelastic properties of the protein increase when the flour has a lower fat content. Hyperprotein quinoa flour could be used to improve the protein content of products such as snacks, pastas, ice cream, bakery products, meat extenders, among others, due to its foaming, gelling or emulsifying capacity. The objective of this work was to study the effect of two types of defatting of hyperprotein quinoa flour on its structural and rheological properties.